Farasan Island of Saudi Arabia confronts the measurable impacts of global warming in 45 years - Khedher, Khaled Mohamed; Abu-Taweel, Gasem Mohammad; Al-Fifi, Zarraq; Qoradi, Mofareh D.; Al-khafaji, Zainab; Halder, Bijay; Bandyopadhyay, Jatisankar; Shahid, Shamsuddin; Essaied, LAATAR; Yaseen, Zaher Mundher (Scientific reports, 2022)
Coastal vulnerability assessment is the key to coastal management and sustainable development. Sea level rise (SLR) and anthropogenic activities have triggered more extreme climatic events and made the coastal region vulnerable in recent decades. Many parts of the world also noticed increased sediment deposition, tidal effects, and changes in the shoreline. Farasan Island, located in the south-eastern part of Saudi Arabia, experienced changes in sediment deposition from the Red Sea in recent years. This study used Digital Shoreline Analysis System (DSAS) to delineate the shoreline changes of Farasan Island during 1975–2020. Multi-temporal Landsat data and DSAS were used for shoreline calculation based on endpoint rate (EPR) and linear regression. Results revealed an increase in vegetation area on the island by 17.18 km 2 during 1975–1989 and then a decrease by 69.85 km 2 during 1990–2020. The built-up land increased by 5.69 km 2 over the study period to accommodate the population growth. The annual temperature showed an increase at a rate of 0.196 °C/year. The sea-level rise caused a shift in the island's shoreline and caused a reduction of land by 80.86 km 2 during 1975–2020. The highly influenced areas by the environmental changes were the north, central, northwest, southwest, and northeast parts of the island. Urban expansion and sea-level rise gradually influence the island ecosystem, which needs proper attention, management, policies, and awareness planning to protect the environment of Farasan Island. Also, the study’s findings could help develop new strategies and plan climate change adaptation.